Effectiveness of Mnemonic Method on Students' Language Information Retention - Belleca, Faith Chi Dy; Caampued, Kristine Roldan; Caballas, Ryan Barrameda; Guiruela, Justine Marie Napiri; Ocampo, Darrel Merenciano (Universitas Kapuas, 2025)
This study aimed to investigate how mnemonic methods, specifically acronyms and acrostics, affect the retention of language information among second-year BSED-ENGLISH students at a state university in Camarines Sur. The research questions focused on the effects of acronyms and acrostics on retention, the effectiveness of mnemonics in improving retention, and differences in post-test results between the comparison and experimental groups, while controlling for pre-test scores. The participants are the 37 respondents from BSED-English 2A and 33 respondents from BSED-English 2B taking the Technical Writing course. A quasi-experimental design used test questionnaires as the primary tool. Statistical methods, including frequency counts, percentages, means, and ANCOVA, were used to analyze the data, revealing significant benefits of mnemonic strategies for short- and long-term retention. The findings emphasized the importance of mnemonics in enhancing language retention. The findings revealed that students exposed to mnemonic strategies, particularly acronyms and acrostics, showed significantly higher retention than those taught through conventional methods. Post-test results indicated that 70.27% of students in the experimental group achieved very high retention, while none fell into low or very low categories. ANCOVA analysis confirmed a statistically significant difference in post-test scores between groups, with a large effect size (partial eta squared = 0.873), affirming the effectiveness of mnemonic methods in enhancing both short- and long-term retention of language information. Educators are urged to incorporate mnemonic techniques to improve retention. Future research could explore the long-term impact of mnemonics across subjects and student groups.